Enhanced recovery for upper gastrointestinal surgery: a review - Evans, Matthew Thomas; Kelliher, Leigh (Digestive Medicine Research; Vol 2 (September 2019): Digestive Medicine Research, 2019)
In recent years, the popularity and application of the ERAS approach has expanded to cover a wide variety of surgical specialties and procedures. This has partly been driven by the ERAS Society, who have published a number of consensus guidelines for surgical procedures including gastrectomy and oesophagectomy. Upper gastrointestinal (GI) surgery includes some of the highest risk elective procedures performed on a routine basis, and consequently, has a lot to gain from the perceived benefits of ERAS. Evidence derived from several recent meta-analyses demonstrates a reduction in hospital length of stay, hospital costs and stress response to surgery through the implementation of ERAS principles in patients undergoing gastrectomy. Although the body of evidence concerning ERAS in oesophagectomy is not as large, analysis of the available data suggests that the application of ERAS principles may result in a reduction of hospital length of stay, pulmonary complications and anastomotic leakage. This review examines the consensus guidelines published by the ERAS Society for both gastrectomy and oesophagectomy and investigates the rationale for some of the recommendations made therein. Both sets of guidelines are comprised of a number of generic ERAS recommendations, common to enhanced recovery programmes across all specialties, as well as specific, evidence-based recommendations applicable to the two surgical procedures concerned. Whilst the advent of these publications represents a significant step forward in the perioperative management of patients undergoing these procedures, many questions still remain. Whether the widespread adoption and implementation of these pathways produces the same magnitude of benefit we have seen elsewhere, for instance in colorectal surgery, remains to be seen, but regardless of that, further research is required to clarify these issues. As new evidence emerges, so the guidelines may be refined and the potential for improving patient’s quality of life and perhaps even overall survival will increase.